2001
DOI: 10.1007/978-1-4757-3333-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Penalty Functions for Optimal Control

Abstract: Abstract:To handle final st ate equality constraints, two ty pe s of pen al ty functions are evaluated a nd compared in solving t hree op timal cont rol pr oblems. Both t he a bsol ute valu e pen al ty func t ion and t he quadra t ic pen al ty fun ction with shift ing terms yielded t he opt imal control policy in each cas e. T he qu adrat ic penal ty fun cti on with shift ing te r ms gave t he optimum more accurately, and t he a pp roach to t he optimum is less oscillatory t han with t he use of abso lute valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Therefore, the inequality expressed by eq 10 becomes equality, and we formulate the augmented performance index to be maximized as where a penalty term is added to the performance index in eq 10. In the penalty function we have included the shifting term s. The advantages of such a penalty function including a shifting parameter to handle equality constraints have been recently demonstrated. , The shifting parameter s is initially set to zero and then is updated after every pass of the optimization procedure according to where q denotes the pass number in the multipass optimization procedure. At the optimum, the factor −2θ s gives the Lagrange multiplier that yields the sensitivity information, showing the effect of changing the volume constraint x 4 ( t f ) = 200.…”
Section: Models Of Typical Fed-batch Reactorsmentioning
confidence: 99%
“…Therefore, the inequality expressed by eq 10 becomes equality, and we formulate the augmented performance index to be maximized as where a penalty term is added to the performance index in eq 10. In the penalty function we have included the shifting term s. The advantages of such a penalty function including a shifting parameter to handle equality constraints have been recently demonstrated. , The shifting parameter s is initially set to zero and then is updated after every pass of the optimization procedure according to where q denotes the pass number in the multipass optimization procedure. At the optimum, the factor −2θ s gives the Lagrange multiplier that yields the sensitivity information, showing the effect of changing the volume constraint x 4 ( t f ) = 200.…”
Section: Models Of Typical Fed-batch Reactorsmentioning
confidence: 99%
“…The use of the quadratic penalty function with a shifting term was introduced by Luus as a way of dealing with difficult equality constraint in steady-state optimization. It was found to be efficient in handling equality state constraints in optimal control problems. …”
Section: Example 1:  Ethanol Fermentation Problemmentioning
confidence: 99%
“…It was found to be efficient in handling equality state constraints in optimal control problems. [16][17][18] To have direct comparison with the results in the literature, 12,14 we chose the final time to be 63.0 h, and we considered the case when the time interval was divided into 20 stages (P ) 20). Hartig et al 12 compared three optimization methods: IDP, sequential quadratic programming (SQP), and the direct search optimization method of Luus and Jaakola 19 (LJ optimization) in solving this problem and reported that IDP yielded the highest success rate with P ) 20.…”
Section: Example 1: Ethanol Fermentation Problemmentioning
confidence: 99%
“…However, it should be noted that the approach recommended here is not restricted to this optimization procedure. Details of the LJ optimization procedure in solving a variety of optimization problems are available in the literature (Luus et al 1995, Luus 2000b,c, 2001. The method can be used successfully for optimization of systems of very high dimension (Luus 1998a).…”
Section: Introductionmentioning
confidence: 98%